Selection of GalNAc-conjugated siRNAs with limited off-target-driven rat hepatotoxicity - Maja M. Janas (Nature Portfolio, 2018)
A subset of chemically-modified siRNAs conjugated to trivalent GalNAc may fail during nonclinical development due to rat hepatotoxicity. Here, the authors show that hepatotoxicity may be accounted for by microRNA-like off-target effects of siRNA and can be mitigated by a thermally destabilizing modification in the siRNA seed region.